Cytoskeleton-Dependent Transport as a Potential Target for Interfering with Post-transcriptional HuR mRNA Regulons - Eberhardt, Wolfgang; Badawi, Amel; Biyanee, Abhiruchi; Pfeilschifter, Josef (Frontiers in Pharmacology, 2016)
The ubiquitous mRNA binding protein human antigen R (HuR), a member of the embryonal lethal abnormal vision (ELAV) protein family has a critical impact on the posttranscriptional control of AU-rich element (ARE) bearing mRNA regulons implied in inflammation, senescence and carcinogenesis. HuR in addition to mRNA stability can affect many other aspects of mRNA processing including splicing, polyadenylation, translation, modulation of miRNA repression and intracellular mRNA trafficking. Since many of the identified HuR mRNA targets (“HuR mRNA regulons”) encode tumor-related proteins, HuR is not only discussed as an useful biomarker but also as promising therapeutic target for treatment of various human cancers. HuR which is most abundantly localized in the nucleus is translocated to the cytoplasm which is fundamental for most of the described HuR functions on target mRNAs. Accordingly, an elevation in cytoplasmic HuR was found in many tumors and correlated with a high grade of malignancy and a poor prognosis of patients. Therefore, direct interference with the intracellular trafficking of HuR offers an attractive approach to intervene with pathologically deregulated HuR functions. Data from several laboratories implicate that the integrity of the cytoskeleton is critical for HuR-mediated intracellular mRNA localization and translation. This review will particularly focus on drugs which have proven a direct inhibitory effect on HuR translocation. Based on the results from those studies, we will also discuss on the principle value of targeting cytoskelton-dependent transport of HuR by natural or synthetic inhibitors as a potential therapeutic avenue for interfering with dysregulated posttranscriptional HuR mRNA regulons and related tumor cell functions. In spite of that, interfering with cytoplasmic HuR transport could highlight a so far underestimated action of microtubule inhibitors clinically used for cancer chemotherapy.